Pandas Basics - Campesato, Oswald (Mercury Learning and Information, 2023)
This book is intended for those who plan to become data scientists as well as anyone who needs to perform data cleaning tasks using Pandas and NumPy. It contains a variety of code samples and features of NumPy and Pandas, and how to write regular expressions. Chapter 3 includes fundamental statistical concepts and Chapter 7 covers data visualization with Matplotlib and Seaborn. Companion files with code are available for downloading from the publisher.FEATURES: Provides the reader with numerous code samples for Pandas and NumPy programming concepts, and an introduction to statistical concepts and data visualization Includes an introductory chapter on Python Companion files with code